Analisis Pengaruh Current Ratio (CR), Debt to Equity Ratio (DER) dan Total Asset Turn Over (Tato) terhadap Return on Assets (ROA) pada PT Unilever Indonesia Tbk Periode 2013-2023 - Risma Dwinna Pratiwi; Titin Agustin Nengsih; Kurniyati Kurniyati (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to determine the influence of Current Ratio, Debt to Equity Ratio (DER) and Total Asset Turn Over (TATO) partially or simultaneously on Return On Assets (ROA). The method in this research uses quantitative methods. The sample selection process can involve purposive sampling techniques, namely determining samples using certain criteria. The financial reports studied for the 2013-2023 period are the financial data of PT Unilever Indonesia Tbk. The type of data used is secondary data. Data analysis techniques use multiple linear regression, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), hypothesis testing (t test and F test) and coefficient of determination (r-square). The results of the research prove that partially the Current Ratio (CR) and Debt to Equity Ratio (DER) have no effect on Return On Assets (ROA), while Total Asset Turn Over (TATO) has a significant effect on Return On Assets (ROA). Simultaneously Current Ratio (CR), Debt to Equity Ratio (DER) and Total Asset Turn Over (TATO) have a significant effect on Return On Assets (ROA).